RETRACTED: Psychological and pedagogical support for children in a children's health camp - Panasenko Anastasia; Panasenko Natalia; Simorin Aleksey (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001